2021
DOI: 10.1186/s13052-020-00935-z
|View full text |Cite
|
Sign up to set email alerts
|

The child with medical complexity

Abstract: Children with medical complexity represent a big challenge for the physicians, their families and the society as well. Although there is no clear definition of this type of patients, they are affected by a chronic, often very severe condition for their whole life. They also represent a huge cost for the health care system due to their needs of continuous assistance.In this review we summarized the definitions of child with medical complexity. Then we illustrated the strategies to treat and take care of these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 18 publications
2
28
0
2
Order By: Relevance
“…In relation to hospital admission rates (0.35%), ICU (0%) and mortality (0%), all values were far lower, significantly, than the population averages. These data do not differ too much from other experiences already published [ 26 , 27 , 28 , 29 ] and reinforce the initial plan that vaccination is not a priority in these groups [ 30 , 31 , 32 ].…”
Section: Discussionsupporting
confidence: 84%
“…In relation to hospital admission rates (0.35%), ICU (0%) and mortality (0%), all values were far lower, significantly, than the population averages. These data do not differ too much from other experiences already published [ 26 , 27 , 28 , 29 ] and reinforce the initial plan that vaccination is not a priority in these groups [ 30 , 31 , 32 ].…”
Section: Discussionsupporting
confidence: 84%
“…The presence of lactoferrin itself and its anti-inflammatory properties perfectly harmonize with anti-viral activities. The important role of lactoferrin is to calm down the cytokine storm, which is the main cause of the rapid course of COVID-19 [ 45 , 46 , 47 , 48 , 49 , 50 , 57 , 79 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 ]. It can be also used to treat osteoporosis because it reduces osteolysis—the destruction of bone cells [ 134 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, various therapies are used to treat COVID-19 that work on the immune system [ 124 , 125 ]. By activating the immune system, dietary supplements can be used as adjuvants with anti-bacterial and immunomodulating properties to inhibit the spread of the COVID-19 virus [ 126 ]. Active substances, which are components of many products include vitamins e.g., vitamin D, probiotics, lactoferrin and zinc, are now extensively clinically tested in patients with COVID-19 respiratory infection [ 127 , 128 , 129 , 130 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that an adequate selenium intake may inhibit SARS-CoV-2 proteases, this being another beneficial effect of selenium in the prevention and treatment of COVID-19 disease [ 166 , 167 ]. Vitamins C, E, and magnesium have also proven to be useful as adjuvants in the therapy against COVID-19, due to their anti-inflammatory and antioxidant properties [ 168 , 169 , 170 , 171 , 172 ].…”
Section: Contribution Of Micronutrients To the Therapy Of Oxidative/inflammatory Diseases Through Their Mitochondrial Actionsmentioning
confidence: 99%